The Effect of Treatment Completion on Recidivism Among TASC Program Clients - Maume, Michael O. (International journal of offender therapy and comparative criminology, 2018)
Despite the enormous resources spent by states in the United States on bridging the gap between criminal justice and behavioral health services, there have been relatively few statewide evaluations of drug treatment client recidivism. We present the results of an evaluation of recidivism outcomes for a sample of individuals (n = 1,274) referred to the Treatment Accountability for Safer Communities (TASC) program in North Carolina from 2007 to 2008. The methodology accounted for both client and offense characteristics drawn from TASC, court, and corrections records. Multivariate analyses indicated that program completion is the most important predictor of re-arrest in the 3-year follow-up period, followed by a number of protective and risk factors. More specifically, being female, older at the time of program entry, as well as higher levels of educational attainment decreased the odds of re-arrest, whereas using crack/cocaine increased the odds of re-arrest. Suggestions for future research and policy implications are provided.